Symbolic Meanings of Prices: Constructing the Value of Contemporary Art in Amsterdam and New York Galleries - Olav Velthuis (Journal of Economic Sociology, 2010)
The paper discusses the results of the sociological analysis of the price setting on the market of contemporary art. Basing on the in-depth interviews with art dealers in New-York and Amsterdam I focus on the two norms of pricing: the first one keeps the dealers from the price declining; the second impels them to set prices in accordance with the size (of the picture).  Relying on these norms I state that price setting is not only economic but also denominative act: despite impersonal business price connotations the actors manage to express a row of cognitive and cultural meanings. Economic theory of signals recognizes that prices have special meanings but reduces their role to the opportunities for getting profit. In humanitarian sciences on the contrary the price meanings have destroying effect. I follow sociological approach according to which the prices, their differences and changes express variety of meanings depending on artist’s reputation, social status of the dealers and the qualities of the art products that are for sale.